RADIKALISME DI DUNIA MAYA: MENEMUKAN TUHAN DI MESIN PENCARIAN - Khoirul Anam (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
This study discusses the important role of the media, especially the Internet as a propaganda tool for the action of radicalism and the spread of terrorism in the name of religion. The virtual world has indeed changed the pattern and the map of radicalism and terrorism, with this technological advancement, terror is no longer only done with disgusting actions through various physical crimes, but also through the doctrination of religiously wrapped religious teachings. If the jelly catches the information, these unfounded abusive doctrines will naturally die. Radicalism and terrorism have indeed leveled up, but that does not mean that its existence can not be destroyed Keywords: Radicalism, Religion and internet